Faktor Yang Mempengaruhi Audit Report Lag Pada Perusahaan Indeks Lq45 Di BEI - Melvin Herlambang, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2021)
This research was conducted to analyze the effect of profitability, liquidity, leverage, and size of Public Accountant to audit report lag on LQ45 Index companies listed in Indonesia Stock Exchange period 2017-2019. The technique used in this research for determining the research sample was purposive sampling. The number of research sample is 27 companies from 32 companies registered as LQ45 Index companies. This research was using quantitative approach. Data analysis method used in this research is multiple linear regression analysis. The result showed that in simultaneously profitability, liquidity, leverage, and size of Public Accountant has a significant effect on audit report lag. Meanwhile, the result of partial research shows that leverage has a negative and significant effect on audit report lag. Profitability, liquidity, and size of Public Accountant has a negative and insignificant effect on audit report lag.